THU0200 Effect of Methotrexate Dose on The Efficacy of Tofacitinib: Treatment Outcomes from A Phase 3 Clinical Trial of Patients with Rheumatoid Arthritis. (15th July 2016) - Fleischmann, R.; Mease, P.; Schwartzman, S.; Hwang, L.-J.; Soma, K.; Connell, C.; Takiya, L.; Bananis, E.
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). ORAL Scan was a 2-year, randomised, Phase 3, clinical trial that evaluated tofacitinib therapy with background methotrexate (MTX) in patients (pts) with RA and an inadequate response (IR) to MTX. 1 Objectives: To study the effect of MTX dose on tofacitinib efficacy in pts from the ORAL Scan study. Methods: In ORAL Scan, MTX-IR pts with RA were randomised 4:4:1:1 to tofacitinib 5 mg twice daily (BID), tofacitinib 10 mg BID, or placebo with advancement to 5 mg BID or to 10 mg BID at Month (Mo) 3 or Mo 6, in combination with background MTX. MTX dose was stable throughout the study and was categorised as Low (≤12.5 mg/week), Medium (>12.5 to <17.5 mg/week), or High (≥17.5 mg/week). Endpoints evaluated at Mo 6 included ACR response rates, proportion of pts achieving low disease activity measured by Clinical Disease Activity Index (CDAI ≤10), CDAI defined remission rate (CDAI ≤2.8), proportion of pts achieving an improvement ≥0.5 in Health Assessment Questionnaire-Disability Index (HAQ-DI), and least squares mean change from baseline in HAQ-DI, Disease Activity Score (DAS28-4[ESR]) and CDAI. Binary variables were evaluated with non-responder imputation, and continuous variables were analysed using a longitudinal model. Regression analyses were conducted to evaluate efficacy responses by MTX dose group and other covariates. Results: 797 pts were randomised and treated (tofacitinib 5 mg BID, n=321; tofacitinib 10 mg BID, n=316; placebo, n=160). In total, 242 pts were included in the Low MTX (9 mg mean) dose group, 333 in the Medium MTX (15 mg mean) dose group, and 222 in the High MTX (21 mg mean) dose group. Baseline demographics and disease characteristics were generally similar across MTX dose groups, though weight, BMI, glucocorticoid (GC) use and CDAI were higher in the High MTX dose group. At Mo 6, greater efficacy was seen with tofacitinib compared with placebo for all endpoints across the 3 MTX dose groups (Table ). Efficacy for placebo-treated pts was generally numerically greater in the Medium and High MTX dose groups than in the Low MTX dose group. Efficacy with tofacitinib appeared similar regardless of MTX dose group. Regression analyses demonstrated a lack of effect of BMI, GC use and MTX dose groups on efficacy assessments. Conclusions: In this post-hoc analysis, clinical efficacy of tofacitinib at Mo 6 was greater than placebo, and appeared similar regardless of MTX dose, as in these pts, tofacitinib was added to patients that had an inadequate response to MTX. Higher MTX doses did not appear to result in additional efficacy to tofacitinib than lower doses. A randomised clinical trial is needed in which different doses of MTX are added to tofacitinib in MTX-naïve pts in order to examine the effect of MTX dose on tofacitinib efficacy. References: van der Heijde D et al. Arthritis Rheumatol 2013; 65: 559–570. Acknowledgement: Previously presented (Fleischmann R et al. Arthritis Rheumatol 2015; 67 (S10): Abstr 1640) and reproduced with permission from Arthritis Rheumatol. This study was funded by Pfizer Inc. Editorial support was provided by S Johnson of CMC, and funded by Pfizer Inc. Disclosure of Interest: R. Fleischmann Grant/research support from: Pfizer Inc, AbbVie, Consultant for: Pfizer Inc, AbbVie, P. Mease Grant/research support from: Pfizer Inc, Speakers bureau: Pfizer Inc, S. Schwartzman Consultant for: Pfizer Inc, L.-J. Hwang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Soma Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Connell Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Takiya Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Bananis: None declared